Method For Increasing The Rate Of Heat Transfer Of Wood Fibres - Gupta, Arun; Sharma, Korada Viswanatha; R. M., Yunus; Kumar, Anuj (2013)
The present invention relates to a method for increasing the rate of heat transfer of wood boards by the use of nano particles of certain metal oxides. The invention relates to increasing the thermal conductivity of wood fibers during manufacturing of wood composites. It reduces the pressing time during production thereby increasing the overall produc tion rate of wood composites and also increasing their strength and Smoothness of Surface.